Venetoclax combined with hypomethylating agents and the CAG regimen in relapsed/refractory AML: a single-center clinical trial - Liu, Yifan; Li, Yanfen; Zhang, Ran; Yu, Zhangyu; Jing, Yu (Frontiers in Immunology, 2023)
This clinical trial (ChiCTR2300075985) evaluated the efficacy of venetoclax in combination with hypomethylating agents and CAG regimens in patients with relapsed/refractory acute myeloid leukemia (R/R AML). Treatment consisted of 400 mg of venetoclax administered orally daily for 14 days as 1 cycle, along with the concurrent administration of hypomethylating agents (decitabine/azacytidine) and CAG (cytarabine, aclarubicin, G-CSF) regimen. The results were as follows: 20 patients with R/R AML were recruited, with a median age of 40 years (10-70), 11 of whom were male (55%), and a median follow-up of 10.4 months (0.7-21.8).The overall response rate (ORR) after receiving 1 course of VEN-DCAG was 90% (18/20), with 17 (85%) CR/CRi (10 MRD-CR), 1 (5%) PR, and 2 (10%) NR. Subsequently, 12 patients (7 MRD-CR, 4 MRD+CR, 1 NR) were treated with the VEN-DCAG regimen, and 3 MRD+CR patients VEN-DCAG in R/R AML turned negative, and 13 patients finally achieved MRD-CR. Among them, 7 patients were in the relapse group, all achieving CR/CRi (6 MRD-CR), and 13 patients in the refractory group, with 10 CR/CRi (7 MRD-CR). The ORR for patients in the relapse and refractory groups was 100% (7/7) and 84.6% (11/13), respectively. Further, all patients experienced adverse events (AEs) of varying degrees of severity, with hematologic AEs primarily consisting of myelosuppression, while non-hematologic AEs were more common in the form of fever, gastrointestinal distress, and infections. 11 patients were followed up with bridging allogeneic hematopoietic stem cell transplantation (allo-HSCT) therapy. At the last follow-up, 11 patients (7 MRD-CR, 4 MRD+CR) who received allo-HSCT, 1 (MRD+CR) died, and 9 patients (6 MRD-CR, 1 PR, 2 NR) who did not receive allo-HSCT, 5 (2 MRD-CR, 1 PR, 2 NR) died as well. Overall, the findings suggest that VEN-DCAG may be an effective treatment option for R/R AML patients. It is recommend that patients should be bridged to allo-HSCT as soon as possible after induction to CR by the VEN-DCAG regimen, which can lead to a significant long-term survival benefit. Clinical trial registration: https://www.chictr.org.cn/, identifier ChiCTR2300075985.